Wideband Microstrip Patch Antenna For Sub 6 GHZ And 5G Applications - Al-Gburi, Ahmed Jamal Abdullah; Mohd Ibrahim, Imran; Zakaria, Zahriladha; Mohd Nazli, Nur Farzana (Wydawnictwo SIGMA-NOT, 2021)
This paper investigates a new shape of microstrip patch antenna designed for the sub 6 GHz range, including a 5G application. The proposed antenna was designed and simulated for the frequencies from 3.5 GHz up to 5 GHz using CST Software. The Rogers RT5880 substrate is used in this study and comes with 0.254 mm thickness and a dielectric constant of 2.2. The proposed antenna feeds by a quarter metallic ground plane attached with a microstrip feed line to improve the antenna impedance mismatch. The effects of the design variation parameters such as the size of the substrate, size of patch and size of the ground plane were observed and analysed in this study. The best antenna parameter was selected based on the return loss antenna performance. Lately, the finalised antenna was successfully simulated in terms of antenna performance.